A Critical Examination of Automation’s Impact on Clinical Judgment and Ethical Care in Technological Dependency in Medicine - Alyami, Saleh Ali Saleh; Alsaab, Mohammed Fahad; Abbas, Banyan Nasser Mana Al; Alyami, Salman Fared Ali; Yami, Turki Abdullh.Dafer Al; Dubais, Ahmad Sale M Mohmmed Al; Shahi, Mohammad Hamad Mahdi Al; Alshahi, Saleh Hussain Ali Al; Alsalem, Mushabbab Ali Mohammed; Dunquwah, Rakan Al (Journal of Ecohumanism, 2024)
The use of technology in healthcare is revolutionizing clinical work and applications such as artificial intelligence, machine learning, and integrations of robotic systems in diagnosing, managing patient data, and treating. Although technology is more accurate, accurate, timely, and economical, there is increased adoption of automation in medicine, and this comes with questions over rationality, ethical considerations, and the human element of treating patients. This paper provides a critical reflection on the impact of automation on clinical reasoning for ethical practice in the context of the growing technology healthcare. Through a review of the available literature and case profiles, this paper aims to explore the opportunities and risks associated with automation in the clinical context and the ethical concerns that arise. The work proves that reliance on technology needs to be closely managed to keep the focus on creating ethical, humane patient care.